How national systems differ in their constraints on corporate executives: a study of CEO effects in three countries - Crossland, Craig; Hambrick, Donald C. (Strategic Management Journal, 2007)
Do CEOs matter more in some countries than in others? Based on a theoretical consideration of three fundamental national‐level institutions—national values, prevailing firm ownership structures, and board governance arrangements—we argue that CEOs in different countries face systematically different degrees of constraint on their latitudes of action, and hence they differ in how much effect they have on firm performance. To test these ideas, we apply a variance components analysis methodology to 15‐year matched samples of 100 U.S. firms, 100 German firms, and 100 Japanese firms. Results provide strong, robust evidence that the effect of CEOs on firm performance—for good and for ill—is substantially greater in U.S. firms than in German and Japanese firms. Copyright © 2007 John Wiley & Sons, Ltd.